Synthesis and Characterization of Some Heterofused Pyrimidine Derivatives - Agarwal, Alka; Bele, D.; Singhvi, I. J. (Asian Journal of Pharmaceutical Research and Development, 2014)
In the present study, a novel series of thiadiazole and thiazolidinone incorporated dihydropyrimidine derivatives (5a-5g) were synthesized starting from different aromatic aldehydes, ethylacetoacetate and urea. The structures of all synthesized compounds were characterized by melting point determination, TLC, elemental analysis, IR, HNMR, C-NMR and LCMS. The LCMS and 13C NMR spectra were recorded only for title compounds.